Increased Concentrations of Serum β-carotene, α-carotene and β-cryptoxanthin Are Associated with Lower Visceral Adipose Tissue in U.S. Adults. (29th May 2020) - Crusan, Ambria; Raatz, Susan; Reicks, Marla; Demmer, Ryan
Abstract: Objectives: There is a positive relationship between visceral adiposity and cardiometabolic diseases (CMD). Recent data report lower serum carotenoids in individuals with obesity. Longitudinal studies show an inverse relationship between CMD and serum carotenoids β-carotene (BC), α-carotene (AC), β-cryptoxanthin (BCX); however, the relationship between serum carotenoids and visceral adiposity in population samples has not been assessed. Our primary objective was to determine the association between adiposity and serum carotenoid concentrations in United States (U.S.) adults. Methods: Data were obtained from 3904 participants in the National Health and Nutrition Examination Survey (2003–2006) using multistage probability sampling. The relationship between android fat percentage (AF%), measured by dual energy x-ray absorptiometry and serum carotenoid concentrations for male and non-pregnant female participants aged 20–85 years in the U.S. was assessed. Associations were estimated using Pearson correlation coefficients and partial correlations adjusting for age, sex, race/ethnicity, and reported carotenoid intake. Multivariable linear regression modeled serum carotenoid concentrations (log transformed) on body fat percentage adjusted for reported dietary carotenoid and total calorie intake, age, sex, and race/ethnicity. Results: Mean ± SE for BC, AC, BCX, and AF% were 12.30 ± 0.05, 2.54 ± 0.07, 6.80 ± 0.04 μg/dL, and 36.87 ± 0.22%, respectively. AF% concentrations were inversely associated with BC ( r = −0.08, P < 0.0001), AC ( r = −0.05, P < 0.0001), and BCX ( r = −0.13, P < 0.0001). Significant ( P < 0.0001) partial correlations were seen among serum levels of all carotenoids and AF%. The strongest was observed with BC where r = −0.23, followed by AC ( r = −0.16), and BCX ( r = −0.14). For adults of the same age, race/ethnicity, and sex, each 1 ug/dL increase in BC or AC concentration decreased AF% by 0.02% ( P < 0.0001). BCX showed significant, but weak associations with AF%. Conclusions: In a representative sample of U.S. adults, serum BC, AC, and BCX concentrations were inversely associated with AF%, independent of reported dietary intake. BC showed the strongest inverse associations followed by AC, then BCX. Funding Sources: N/A.